Colorectal cancer and country of birth in New South Wales, Australia: All-of-population data for prioritising health service delivery and research. (October 2022) - Zhao, George W.; Roder, David M.; White, Sarah; Lin, Enmoore; Challam, Sheetal; Little, Alana; Renzaho, Andre; Pitts, Leissa; Liauw, Winston; Currow, David
Abstract: Introduction: Cancer care and outcomes differ across cultural groups in Australia. Quantifying these differences facilitates prioritisation and targeting of services and research. All-of-population data are needed by health agencies to understand and fulfil their cancer-control responsibilities. Compiling these data can be challenging while maintaining privacy. We have used data linkage to gain population-wide colorectal cancer data on stage (degree of spread), treatment, and survival in New South Wales (NSW), Australia, by country of birth (COB), and consider service implications. Methods: We studied colon and rectal cancers diagnosed in 2003–2016 and recorded on the NSW Cancer Registry (n = 41, 575), plus linked hospital data and data from Australian Medical and Pharmaceutical Benefits payments, other treatment data and death records. Outcomes for 12 COB categories were analysed using multiple logistic and proportional hazards regression, with Australia as the reference category. Results: Compared with Australian born, the adjusted odds ratio for distant spread of colon cancer was higher for people born in Lebanon and the United Kingdom. Treatment was less common for people born in China (surgery), Germany (systemic), Italy (surgery), New Zealand (any treatment) and Vietnam (all treatments), while treatment for rectal cancer was more common for people born in Italy (surgery), United Kingdom (radiotherapy, systemic therapy), and Vietnam (surgery), and less frequent for people born in China (radiotherapy). Adjusted 5-year survival was higher for people born in China, Italy, Vietnam, Greece (colon), Lebanon (colon) and other non-English speaking countries. More advanced stage was negatively related to having surgery and survival. Conclusions: This study illustrates how linked data can enable comparisons of multiple outcomes for colorectal cancer by country of birth across an entire population. Results disclose "big picture" variations in population characteristics, stage, treatment and survival. This will enable better targeting and prioritisation of services and inform research priorities to address disparities. Highlights: NSW seeks population-wide data to inform cancer control planning and research. Data linkage provides the required population breadth while protecting privacy. Differences in colorectal cancer present in this study by country of birth (COB). Differences by COB present by stage, treatment exposures, and survival outcomes. These differences can inform remedial service plans and future research directions.